2017
DOI: 10.21608/adjg.2017.5258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanostuctured Hydroxyapetite Incorporation into a Resin Composite on Shear Bond Strength to Dentin and Interfacial Micromorphology after Storage in Different Media

Abstract: Aim: This study was designed to evaluate the effect of incorporation of hydroxyapatite nanorods into a resin composite restorative material and dental adhesive on shear bond strength to dentin and interfacial micromorphology after storage in different media. Materials and Methods: Ninety natural premolars (N=90) were selected for this study and randomly divided into three main groups (n =30) according to the material used (A), where A1: the resin composite restorative material reinforced with hydroxyapatite na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Moreover, the microtensile bond strength values were higher after storage in artificial saliva in all groups, because artificial saliva contains many minerals like Ca++, PO4--, Na+ and urea. During storage, deposition of these minerals on the surface Effect of Egg Shell and White Tea Dentin Pretreatment on Microtensile Bond Strength (407) resulted in the formation of film probably composed of calcium which prevents hydrolytic degradation of the collagen fibrils which results in an increase in the bond strength (36) . On the contrary, it was found that the microtensile bond strength values decreased after storage which may be due to storage in water leading to the degradation of resin -dentin bond strength by time (37) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the microtensile bond strength values were higher after storage in artificial saliva in all groups, because artificial saliva contains many minerals like Ca++, PO4--, Na+ and urea. During storage, deposition of these minerals on the surface Effect of Egg Shell and White Tea Dentin Pretreatment on Microtensile Bond Strength (407) resulted in the formation of film probably composed of calcium which prevents hydrolytic degradation of the collagen fibrils which results in an increase in the bond strength (36) . On the contrary, it was found that the microtensile bond strength values decreased after storage which may be due to storage in water leading to the degradation of resin -dentin bond strength by time (37) .…”
Section: Discussionmentioning
confidence: 99%